2020
DOI: 10.1063/5.0003330
|View full text |Cite
|
Sign up to set email alerts
|

Label-free deeply subwavelength optical microscopy

Abstract: We report the experimental demonstration of deeply subwavelength far-field optical microscopy of unlabelled samples. We beat the ~λ/2 diffraction limit of conventional optical microscopy several times over by recording the intensity pattern of coherent light scattered from the object into the far-field. We retrieve information about the object with a deep learning neural network trained on scattering events from a large set of known objects. The microscopy retrieves dimensions of the imaged object probabilisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Optimal and precise manipulation of the pupil function, beyond conventional optics, may be possible with the advent of amenable metasurfaces [16][17][18]20]. More work on ACI and potential relevance with structured illumination microscopy [3,[49][50][51][52][53], superoscillatory imaging [79][80][81][82][83], and super-gain [84,85] can enrich further understanding of imaging beyond the known boundaries. Computational superresolution techniques [42][43][44][58][59][60] integrated with ACI can provide extended resolution limits.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal and precise manipulation of the pupil function, beyond conventional optics, may be possible with the advent of amenable metasurfaces [16][17][18]20]. More work on ACI and potential relevance with structured illumination microscopy [3,[49][50][51][52][53], superoscillatory imaging [79][80][81][82][83], and super-gain [84,85] can enrich further understanding of imaging beyond the known boundaries. Computational superresolution techniques [42][43][44][58][59][60] integrated with ACI can provide extended resolution limits.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Pu et al [65,81] (Figure 4c) have shown that the combination of machine learning with photonics can revolutionize one of the most important field in optics, imaging. In a theoretical article [65], they first introduced a new imaging technique termed Deeply Subwavelength Superoscillatory Imaging (DSSI) that has the potential to reveal the fine structure of a physical object through its farfield scattering pattern under superoscillatory illumination with a resolution far beyond the conventional "diffraction limit" exceeding λ/200 for a dimer comprising two subwavelength opaque particles.…”
Section: Ai In Photonics and Nanophotonicsmentioning
confidence: 99%
“…In a theoretical article [65], they first introduced a new imaging technique termed Deeply Subwavelength Superoscillatory Imaging (DSSI) that has the potential to reveal the fine structure of a physical object through its farfield scattering pattern under superoscillatory illumination with a resolution far beyond the conventional "diffraction limit" exceeding λ/200 for a dimer comprising two subwavelength opaque particles. Then, they have demonstrated this new imaging technique experimentally [81] by retrieving the parameters of a physical object from its scattering pattern with resolution exceeding λ/20. And in an application of AI to optical metrology, Rendón-Barraza et al [82] have demonstrated how the physical size of subwavelength objects can be determined with accuracy exceeding λ/800 via a deep learning-enabled analysis of diffraction patterns.…”
Section: Ai In Photonics and Nanophotonicsmentioning
confidence: 99%
“…Very recently, it was demonstrated that far‐field, noncontact, label‐free, optical, high‐resolution imaging can be achieved by analyzing intensity patterns of light scattered by the object using artificial intelligence. [ 5,6 ] Here we demonstrate by virtue of numerical and proof‐of‐principle real‐life experiments that further improvement in resolution can be achieved by illuminating the object with topologically structured light. The improved resolution results from the interactions of the object's fine features with singularities of highly structured topological light.…”
Section: Introductionmentioning
confidence: 99%